A cost-effectiveness analysis of condom distribution programmes for the prevention of sexually transmitted infections in England. Issue 9 (5th July 2017) - Sadler, Susannah; Tosh, Jon; Pennington, Rebekah; Rawdin, Andrew; Squires, Hazel; Romero, Carmen; Fischer, Alastair; Chilcott, James
Abstract : Background: Prevention of sexually transmitted infection (STI) incidence in England is a high priority, particularly among young people, men who have sex with men (MSM) and black ethnic minorities. An economic evaluation of condom distribution programmes (CDPs) to reduce STI transmission is presented. Methods: An economic model using a Bernoulli process estimated the number of people acquiring an STI as a function of its prevalence, transmission rate, condom use, condom failure rate and number of sexual contacts. Models were developed for young people (13–24 years), black ethnic minorities, MSM and the general English population. Effectiveness evidence came from a recent systematic review. For young people, a CDP was modelled (relative risk for condom use=1.23), along with an exploratory analysis of the impact on unintended pregnancies. For other populations, threshold analyses were used to identify the combination of costs and effect size required to make a programme cost-effective. Results: The base case predicted that CDP for all young people in England could avert 5123 STI cases per annum, with an incremental cost–effectiveness ratio of £17 411. In addition, it could avert 118 pregnancies and 82 abortions and save £333 000 in associated costs. Schemes for black ethnic minorities and MSM could also be cost-effective even with relatively high costs and small effect sizes. Conclusion: CDPs for young people are likely to be cost-effective or cost-saving. CDPs for other high-risk populations may also be cost-effective if they can increase condom use, since high HIV prevalence in these groups imposes a considerable health and cost burden.